The Role of Curators in Bankruptcy Legal Issues Between Debtors and Creditors in Postponement of Debt Payment Obligations (PKPU) - Noviriska; Dwi Atmoko (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2024)
In accordance with article 37 of 2004 concerning bankruptcy and suspension of debt payment obligations (PKPU) Bankruptcy article 1 which explains that a creditor is a person who has receivables due to an agreement or law that can be collected in court. A debtor is a person who has debts due to an agreement or law whose payment can be collected in court. A bankrupt debtor is a debtor who has been declared bankrupt by a court decision. The Curator is the Estate Office or an individual appointed by the Court to manage and settle the assets of the Bankrupt Debtor under the supervision of the Supervisory Judge in accordance with this Law. Debt is an obligation that is stated or can be stated in an amount of money either in Indonesian currency or foreign currency, either directly or which will arise in the future or contingently, which arises due to an agreement or law and which must be fulfilled by the Debtor and if not fulfilled gives the Creditor the right to obtain fulfillment from the Debtor's assets. In the event of bankruptcy, the curator has full authority after the bankruptcy decision is issued by the Judge. The curator's responsibilities are divided into 2 (two), namely the responsibility as a curator in his capacity as a curator, and the responsibility of the curator in his capacity not as a curator. The role of the curator in postponing debt payment obligations is to manage and distribute the debtor's assets to creditors in accordance with the regulations and priorities stipulated in the Bankruptcy Law. The curator also ensures that payments are made fairly and in accordance with the law. The duties and roles of the curator in the bankruptcy process are 1) Managing the debtor's assets after the debtor no longer has the authority to manage the assets. 2) Managing and settling the bankruptcy estate from the date the bankruptcy decision was pronounced. 3) Revealing bank secrets to obtain complete information regarding the debtor's assets. 4) Carrying out execution of all debtor assets that are outside the jurisdiction of Indonesia In carrying out his duties, the curator will be supervised by a supervising judge. The supervising judge is tasked with supervising the authority and implementation of the curator's duties so that he always carries out his authority and duties within the specified limits.